Charade - Donen, Stanley; Stone, Peter, 1930-2003; Grant, Cary, 1904-1986; Hepburn, Audrey, 1929-1993; Matthau, Walter; Coburn, James; Kennedy, George; Minot, Dominique; Glass, Ned; Marin, Jacques, 1919-2001; Bonifas, Paul; Stewart, James, 1908-1997; et al. (Universal City, CA : Universal Studios, 2012)
Charade: An American woman in Paris finds her husband murdered and soon is pursued by three strange men, with only a handsome, suspicious stranger to help her.
Charade: Originally released as a motion picture in 1963
"100 years of Universal."
Charade: Cary Grant, Audrey Hepburn, Walter Matthau, James Coburn, George Kennedy, Dominique Minot, Ned Glass.
Charade: DVD, Dolby digital 2.0 mono, anamorphic widescreen 1.85:1.
In English or French with optional English, French, or Spanish subtitles.
Subtitled for the deaf and hard of hearing.
Keywords: Criminals -- Fiction; Murder -- Fiction; Feature films; Drama; Fiction